Decentralization of financial administration: Analysis of the creation of executing management units within the scope of the PMPA - Nascimento, Heyder Silva do; Silva, José Vicente Braga da (Seven Editora, 2024)
The article analyzes financial administration within the Military Police of Pará (PMPA), from the perspective of decentralization through the creation of new executing management units (UGEs). The research had the general objective of analyzing this decentralization as an instrument of excellence and innovation for the budgetary and financial management of the Corporation. The problem asks whether there are factors that justify the implementation of UGEs, making financial execution more efficient. A qualitative approach was adopted, with technical procedures of bibliographic and documentary research. The results revealed that PMPA's budget increased by 48.8% between 2019-2022, however the total commitments grew less. In addition, expenses with allowances and supplies represent most commitments, although they are a small part of the total executed. This demonstrates excessive centralization and lack of criteria in the allocation of resources. Thus, the analysis indicates problems such as possible underutilization of the budget, concentration of commitments in allowance/supply expenses and lack of systematic planning in resource allocation. It is concluded that decentralization through UGEs is necessary to modernize and improve PMPA's financial administration, providing greater efficiency, transparency, and control over the process. UGEs would allow better budget planning and execution by local managers, according to the specific demands of the regions and operational activities. The research proves that financial decentralization in PMPA could bring managerial and compliance benefits. DOI:https://doi.org/10.56238/sevened2023.006-104